Body pressure prediction for pressure ulcer prevention in a bed head elevation operation. (16th February 2021) - Kosuge, M.; Ishihara, Y.; Takahashi, M.
ABSTRACT: Pressure ulcers are caused by tissue damage, which occurs when the blood supply to an area of skin is diminished because of sustained or concentrated pressure on a patient from the mattresses of a bed. One action that concentrates the pressure is a bed head elevation operation. Recently, a control system known as the alternative pressure mattress has been proposed to prevent the concentration of pressure. However, the challenge with this controlled system is that it has a slow response because it uses air cells. The slow response causes controlling the air cells to lag behind the change in pressure during the bed head elevation operation. Therefore, this system cannot adequately prevent the concentration of pressure on a patient. To address this issue, we need to predict the change in pressure during the bed head elevation operation and control the pressure based on this prediction. In the current work, we focus on predicting the pressure distribution. This prediction is high-dimensional. We regarded the pressure distribution as an image and predicted the change in pressure by applying a deep neural network. To the best of our knowledge, this paper is the first to propose the body pressure predictive model. GRAPHICAL ABSTRACT: UF0001